Saksi sa kasaysayan [videorecording], Part I Erap sa harap ng pagsubok - Estrada, Joseph; I Witness (Quezon City GMA Network, Inc., 2001)
The life of Joseph Estrada as President of the Philippines
GMA Network's Coverage of the Impeachment Trial and People Power II.
with DVD copy (CD-001291)
Keywords: President of the Philippines -- Estrada, Joseph